THE IMPACT OF MERGER AND ACQUISITION ON FINANCIAL PERFORMANCE IN INDONESIA - Zuhri, Saefudin; Fahlevi, Mochammad; Abdi, Muhammad Nur; Irma, Dasih; Maemunah, Sari (Journal of Research in Business, Economics, and Education, 2020)
Merger and Acquisition are two forms of the business combination, where companies that take assets and liabilities or controls are called acquiring companies or bidders, while companies that are taken over are called target companies. The results of the statistical analysis of the Wilcoxon signed-rank test found that there was no significant difference in Return on Equity and Debt to Equity Ratio financial ratios before and after Merger and Acquisition. We can even see that the median and average of pre- Merger and Acquisition Return on Equity is greater than the post- Merger and Acquisition Return on Equity, the same thing is also obtained from the results of this test that we can even see the median and average before the occurrence of Merger and Acquisition had a smaller ratio and was considered better.